Edge Effect on the Photodetection Ability of the Graphene Nanocrystallites Embedded Carbon Film Coated on p‐Silicon. Issue 6 (14th February 2019) - Zhang, Xi; Peng, Da; Lin, Zezhou; Chen, Wencong; Diao, Dongfeng
Abstract : A sensitive photodetector of graphene nanocrystallites embedded carbon (GNEC) film coated on p‐silicon has been proposed. Different from the conventional growth mode of graphene, GNEC film contains a large amount of vertically grown graphene nanocrystallites (GNs). Edges of GNs act as electron trapping centers, increasing the ability to capture electrons. Different types of films are prepared under various deposition biases (20, 40, 60, and 80 V), which have different density of edges ( N edge ). Edge entrapment improves the photocurrent responsivity of 40 V film (high N edge ) to 0.401 A W −1, compared with 0.126 A W −1 of 20 V film (amorphous, no N edge ) and 0.194 A W −1 of 80 V film (low N edge ). A high specific detectivity of 1.34 × 10 12 cm Hz 1/2 W −1 is exhibited at zero bias. GNs maintain a charge transport channel, which makes it have a fast response time τ rise = 260 ns. Abstract : A photodetector of vertically grown graphene nanocrystallites embedded carbon films on p‐type silicon is proposed with a high responsivity of 0.401 A W −1 and fast response of 260 ns. Edges play the role of electron trapping centers in the photovoltaic process.